Differential mixer with NMOS/PMOS stack at switching stage - Martins, Everson [UNESP]; Alejandro, Matheus A. [UNESP]; Fogaça, Thaís V. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper proposes a novel differential mixer topology. The traditional stage of switching is replaced by a stack of NMOS and PMOS transistors combined. A design is given of a 900 MHz down-conversion mixer using a 0.35 μm CMOS process. Comparison with conventional mixer shows that the topology leads to a better performance in terms of conversion gain and linearity. ©2012 IEEE.
Keywords: CMOS inverter; CMOS mixer; Differential mixer; 900 MHz; CMOS inverters; CMOS processs; Conversion gain; Downconversion mixer; Mixer topology; pMOS transistors; Switching stage; CMOS integrated circuits; Integrated circuits; Mixing; Systems analysis; Topology; Mixers (machinery)